Rancang Bangun Sistem Informasi Pemeliharaan Lokomotif Kereta Api - Magdhalena, Yurike; Sunarto, M. J. Dewiyani; Lemantara, Julianto (Jurnal JSIKA, 2013)
Dipo Locomotive Sidotopo is the place that is used to maintenance the train locomotives. Now, Dipo officer schedules locomotives maintenance without considering the lifetime of aspects in each locomotive. Besides, the  locomotives maintenance information is not available, and the locomotives usage is not record well. The existing locomotives are old, this case makes locomotives operational dangerous and threats the safety of passengers. Based on the problem, this research will design and implement information system to maintenance the train locomotives to provide information about locomotives maintenance with considering the usage of aspects in each locomotive. This information system is built on web-based and Short Message Service (SMS) Gateway. The web is used to provide an integrated information about maintenance, while SMS Gateway is used to give alert about maintenance needs. The research result showed that this information system can provide the correct calculation based on kilometers usage in every aspects of each locomotives, and can provide an alert through SMS at the right time. This information system can also help the Dipo Locomotives Sidotopo and other train stations to entry the data and the latest status of the locomotives in an integrated way. Keywords : information system, train locomotive, web, SMS Gateway